Influence Servitization And Electronic Word of Mouth (E-Wom) on Buying Intention With Consumer Trust as Mediation - Anggres Ayu Damayanti; Sidiq Permono Nugroho (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
The purpose of this study was to analyze the effect of Servitization and E-Wom on Purchase Intention with Consumer Trust as Mediation. The type of research used in the study is causal associative research using quantitative techniques. The population in this study were customers of various coffee shops in Surakarta. The sampling technique used is purposive sampling. The technique for determining the number of samples can use the Lemeshow Formula. By using the Lemeshow formula obtained is 96.04 which is then rounded up to 100 people. The analysis technique used is Partial Least Square (PLS) with the calculation process assisted by the SmartPLS 3.0 software program. The results of this study show that Servitization, E-Wom, and Trust have a positive and significant effect on purchase intention. Trust has a positive and significant effect on purchase intention. Servitization and E-wom have a positive and significant effect on customer trust. Trust mediates the effect of Servitization on purchase intention. Trust mediates the effect of servitization on purchase intention